The effects of electrical pulses-mediated gold and silver nanoparticles on the optical properties of ex vivo human femoral head tissue with optical coherence tomography. (5th July 2021) - an, Ran; Gu, Huaimin; Wei, Huajiang; Zhuang, Ze; Ren, Jianhua; Guo, Zhouyi; He, Yonghong; Xie, Shusen; Yang, Hongqin
Abstract: This study aims to monitor and assess the penetration and accumulation of gold nanoparticles (Au NPs) or silver nanoparticles (Ag NPs) (average particle size 40 nm) and the penetration of the Au NPs or Ag NPs assisted by electrical impulses (EP) in human normal femoral head (NFH) and pathological femoral head (PFH) tissues. The results show that optical coherence tomography images can easily distinguish NFH from PFH tissues. The control group show that the average attenuation coefficient of NFH tissue is 4.895 mm −1, and the average attenuation coefficient of PFH tissue is 8.094 mm −1 . It shows that the average attenuation coefficient of PFH tissue is significantly greater than that of NFH tissue. High frequency EPS can promote the penetration of nanoparticles into tissues more than low frequency EPS, and the attenuation coefficients of tissues are reduced by 27.31% and 40.35%, respectively. The average attenuation coefficient of PHF tissue changes from 7.75 ± 0.26 mm −1 to 7.60 ± 0.13 mm −1 and 7.93 ± 0.20 mm −1 to 6.94 ± 0.18 mm −1 at 150 min for Ag NPs and Ag NPs/EP treatment, respectively. The attenuation coefficient is reduced by 2.00% and 12.48% respectively. The results suggest that the optical properties of PFH tissues are greatly influenced by Ag NPs and their combination with EP.